Women in Leadership in State and Regional Orthopaedic Societies. (5th April 2022) - Ramos, Tolulope; Daban, Roxanne; Kale, Nisha; Brown, Symone; Miskimin, Cadence; Cannada, Lisa K.; Mulcahey, Mary K.
Abstract : Introduction: Female representation in orthopaedics remains low compared with other specialties. Recently, several studies have examined the membership composition and leadership roles of women in orthopaedic societies. However, there is a paucity of information on the possible connection between the number of women within state and regional orthopaedic societies and women who serve in leadership roles within these societies. Methods: Authors invited executive directors of 51 state and four regional orthopaedic societies to participate in an anonymous 14-question web-based survey about female members and women in leadership positions within these societies. The survey asked about female membership composition, the percentage of male and female practicing orthopaedic surgeons in the state/region (if available), and female representation on the Board of Directors of these societies. Data were analyzed for relationships between ordinal variables. Results: Forty-nine executive directors (89.1%) responded to the survey. Among respondents, there was a statistically significant positive correlation between the percentage of female members and women leaders ( P = 0.015). Thirty-two executive directors (68.1%) reported between 1% and 10% female members, 7 (14.9%) had between 11% and 20% female members, and 2 (4.3%) had no female members. Twenty-five societies (52.1%) have never had a female president. Of 17 societies (32.7%) that had female presidents, 15 (75.0%) reported having just one female president. In addition, of these 17 societies, 12 (70.6%) reported having at least one acting female president within the past 10 years. Discussion: Our study demonstrates a positive correlation between female members and women on the Board of Directors in regional and state orthopaedic societies. Twelve societies had female presidents within the past 10 years. Female representation in leadership positions may help with the recruitment of female orthopaedic surgeons and improve diversity in orthopaedics. Future studies should evaluate different methods of increasing female membership and leadership positions in state and regional orthopaedic societies.